2015
DOI: 10.1063/1.4931914
|View full text |Cite
|
Sign up to set email alerts
|

High power cascaded mid-infrared InAs/GaSb light emitting diodes on mismatched GaAs

Abstract: InAs/GaSb mid-wave, cascaded superlattice light emitting diodes are found to give higher radiance when epitaxially grown on mismatched GaAs substrates compared to lattice-matched GaSb substrates. Peak radiances of 0.69 W/cm2-sr and 1.06 W/cm2-sr for the 100 × 100 μm2 GaSb and GaAs-based devices, respectively, were measured at 77 K. Measurement of the recombination coefficients shows the shorter Shockley-Read-Hall recombination lifetime as misfit dislocations for growth on GaAs degrade the quantum efficiency on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recent work from the same group on LEDs grown on GaAs shows a higher performance at 77 K than comparable devices on GaSb, despite high dislocation density on the GaAs wafers [144], while the Shockley-Read-Hall recombination was significant at a low injection current for typical operating current densities (100-1000 A cm −2 ). The superior thermal conductivity and lower IR absorbance of GaAs compared to GaSb enabled higher external quantum efficiency for dislocated devices on GaAs.…”
Section: Type-ii Superlattice-based Mid-ir Emitters On Inas and Gasb mentioning
confidence: 94%
“…Recent work from the same group on LEDs grown on GaAs shows a higher performance at 77 K than comparable devices on GaSb, despite high dislocation density on the GaAs wafers [144], while the Shockley-Read-Hall recombination was significant at a low injection current for typical operating current densities (100-1000 A cm −2 ). The superior thermal conductivity and lower IR absorbance of GaAs compared to GaSb enabled higher external quantum efficiency for dislocated devices on GaAs.…”
Section: Type-ii Superlattice-based Mid-ir Emitters On Inas and Gasb mentioning
confidence: 94%
“…The InAs/GaSb-based active region was grown as described in previous work from this group . The transition layers used to grow the active region onto lattice-mismatched GaAs are also detailed in previous work . The stack was grown to have an emission wavelength of λ = 3.6 μm at 77 K. The measured wavelength from photoluminescence measurements of the wafer was centered at λ = 3.5 μm at 77 K, with a full-width at half-maximum (FWHM) of approximately 0.25 μm.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, Provence et al . [ 81 ] showed that SL-LEDs grown on mismatched GaAs substrate exhibited higher radiance than those grown on lattice GaSb substrates at a measurement temperature of 77 K. The higher emission power of GaAs substrates can be explained due to the lower absorption of light in the MIR region as well as the better thermal properties of the GaAs substrate compared to GaSb. Furthermore, measurement of recombination coefficients revealed that the shorter Shockley–Read–Hall recombination lifetime of the dislocation defects when grown on GaAs affects quantum efficiency only at low current injection.…”
Section: Advancements In Mir Light Sources Beyond Lasersmentioning
confidence: 99%